2021
DOI: 10.13057/biodiv/d220921
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of Octolasmis spp. parasites in mud crabs Scylla spp. as a bioindicator for mercury pollution

Abstract: Abstract. Nur I, Aris EA, Yusnaini Y, Beavis S. 2021. The potential use of Octolasmis spp. parasites in mud crabs Scylla spp. as a bioindicator for mercury pollution. Biodiversitas 22: 3764-3772. Artisanal small-scale gold mining and the use of mercury is widespread across Indonesia, often characterized by relatively short-lived gold rushes. In the late and post-mining phases, mercury stored in mine tailings and river beds was transported down catchment, posing risks to ecosystems and human health over much lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…Gastropods and crabs play a role in food webs in aquatic ecosystems (Batvari et al 2016). Gastropods and crabs are often used as ecosystem bioindicators because they live attached to the substrate and at the bottom of the water (mud and sand), which causes direct contact with pollutants that enter their habitat (Sharma et al 2018;Nur et al 2021;Sueb et al 2021). Gastropods and crabs also have relatively long and sedentary life cycles, so they can be used to detect ecosystem temporal and spatial changes (Shaiek et al 2018;Afwanudin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Gastropods and crabs play a role in food webs in aquatic ecosystems (Batvari et al 2016). Gastropods and crabs are often used as ecosystem bioindicators because they live attached to the substrate and at the bottom of the water (mud and sand), which causes direct contact with pollutants that enter their habitat (Sharma et al 2018;Nur et al 2021;Sueb et al 2021). Gastropods and crabs also have relatively long and sedentary life cycles, so they can be used to detect ecosystem temporal and spatial changes (Shaiek et al 2018;Afwanudin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Bojko et al (2022) reported the presence of parasites from a group of viruses in the intestinal epithelium, ciliated protozoa in the gill lamellae, fungi in the gonads, and metazoan ectoparasites in the gills of the Aratus pisonii mangrove crab. Nur et al (2021) reported parasites from the phytoplankton arthropods Octolasmis spp. on mangrove Scylla spp.…”
Section: Distribution Of Crustaceans In the Mangroves Of Nusa Lembonganmentioning
confidence: 99%